The Application of Preoperative Three-Dimensional Reconstruction Visualization Digital Technology in the Surgical Treatment of Hepatic Echinococcosis in Tibet - Zhang, Jun; DAWA,; Suolang, Duojie; Lei, Yanming; Wang, Jiayun; Basang, Dunzhu (Frontiers in Surgery, 2021)
Objective: The present study aims to explore the application value of three-dimensional (3D) reconstruction technology in the preoperative evaluation of patients with complicated hepatic echinococcosis in Tibet. Methods: A total of 200 patients with complicated hepatic echinococcosis, admitted to our hospital between May 2019 and December 2020, who underwent radical hepatectomy, were enrolled in the present study. The patients were randomly divided into a preoperative computer tomography group and a preoperative 3D reconstruction group. According to the imaging results, a surgical plan was formulated. A comparison was made between the two groups of the coincidence rate of the surgical plan and intraoperative and postoperative complications. Results: The patients with hepatic echinococcosis who underwent 3D visualization reconstruction before surgery had a high compliance rate with the surgical plans and the operating time, the number of cases with blood flow blockage, the blood flow blockage time, intraoperative hemorrhage, and postoperative biliary fistulas were significantly lower. Conclusion: The application of preoperative 3D visualization reconstruction in patients with complicated hepatic echinococcosis in Tibet could effectively improve surgical safety.